10 kHz cervical SCS for chronic neck and upper limb pain: 12 months' results. Issue 11 (8th October 2019) - El Majdoub, Faycal; Neudorfer, Clemens; Richter, Ronald; Schieferdecker, Simon; Maarouf, Mohammad
Abstract: Objective: Spinal Cord Stimulation (SCS) overlaps painful areas with paresthesia to alleviate pain. Ten kHz High‐Frequency SCS (HF10 cSCS) constitutes a treatment option that can provide pain relief without inducing paresthesia. In this retrospective, open‐label study, we evaluated the efficacy of HF10 cSCS in chronic neck and/or upper limb pain. Methods: Between May 2015 and August 2017, 24 consecutive patients with neck and/or upper limb pain were treated with HF10 cSCS. The patients' mean age was 61.4 years (range: 40.1–82.6 years). The mean neck and upper limb pain at baseline was 8.8 (range: 7.0–10) and 7.5 (range: 6.0–9.0) according to the visual analog scale (VAS). Functionality was evaluated using the Oswestry Disability Index (ODI). To assess health‐related psychological impairment, we used the Global Assessment of Functioning questionnaire. Results: Twenty‐three patients responded to treatment. Pain intensity reduced significantly to a mean score of VAS 2.5 (range: 2.0–4.0) for neck and 2.0 (range: 1.0–3.0) for upper limb pain after 6 months. At 12 months, VAS scores for neck and upper limb pain reduced to 2.2 (range: 1.0–3.0) and 1.7 (range: 1.0–3.0), respectively. Mean ODI scores decreased from 31 (range: 21–42) at baseline to 19.9 (range: 8–26) after 12 months. In three patients, infection of the IPG pocket occurred r and 8.7 months after surgery. One patient has had lead migration resulting in a surgical revision. Interpretation: HF10 cSCS therapy has proven to be effective in reducing neck and upper limb pain significantly and increasing functional capacity. These results warrant further studies with larger patient series and longer follow‐ups.